2016
DOI: 10.4172/2472-0895.1000112
|View full text |Cite
|
Sign up to set email alerts
|

Early Atherosclerotic Changes in the Patients with Idiopathic Epilepsy: Egyptian Preliminary Study

Abstract: Background: Patients with epilepsy are at higher risk for atherosclerosis which may be due to epilepsy or antiepileptic drugs. The frequency of atherosclerosis in patients with epilepsy was not previously studied in Egypt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…5 It was found that cytochrome P450 enzyme induction might reduce the feedback inhibition of 3-hydroxy-3methylglutaryl coenzyme A synthesis, and subsequently resulted in increasing the level of cholesterol. 35 It was found that epileptic patients maintained on carbamazepine or valproate monotherapy-as in our studyhave increased cholesterol and TG concentrations. 36 The role of AEDs in the pathogenesis of atherosclerosis is not fully understood.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…5 It was found that cytochrome P450 enzyme induction might reduce the feedback inhibition of 3-hydroxy-3methylglutaryl coenzyme A synthesis, and subsequently resulted in increasing the level of cholesterol. 35 It was found that epileptic patients maintained on carbamazepine or valproate monotherapy-as in our studyhave increased cholesterol and TG concentrations. 36 The role of AEDs in the pathogenesis of atherosclerosis is not fully understood.…”
Section: Discussionsupporting
confidence: 67%
“…It was found that cytochrome P450 enzyme induction might reduce the feedback inhibition of 3-hydroxy-3- methylglutaryl coenzyme A synthesis, and subsequently resulted in increasing the level of cholesterol. 35 …”
Section: Discussionmentioning
confidence: 99%